Early experience with transcatheter ventricular septal defects closure with the KONAR-MF multifunctional occluder - Elafifi, Abdelrahman; Kotit, Susy; Shehata, Mahmoud; Deyaa, Omar; Ramadan, Asmaa; Tawfik, Mohammad (Frontiers in Pediatrics, 2025)
IntroductionTranscatheter device closure of ventricular septal defects (VSDs) offers an appealing and effective alternative to surgical repair. The Lifetech™ Konar-Multifunctional Occluder (MFO) VSD occluder has gained increasing application due to its versatility and promising outcomes.ObjectivesWe aim to evaluate our experience with the MFO device for VSD closure.MethodsWe conducted a prospective analysis of clinical data from 151 patients who underwent percutaneous closure of muscular and perimembranous VSDs using the MFO device at our institution between November 2018 and September 2023. Comprehensive assessments of safety and procedural outcomes were performed.ResultsThe patient's mean age was 55.4 ± 51.6 months (range, 6 months to 31 years), and the mean weight was 17.6 ± 11.9 kg (range, 5–86). Among the patients, 94 (62.3%) had perimembranous defects, while the remaining had muscular VSDs. The mean defect diameter was 4.8 ± 1.5 mm (range, 2–10). The retrograde approach was applied in 133 patients (88.7%). Device implantation was successful in 98.7% of patients. One procedure (0.7%) failed due to device migration, requiring surgical retrieval and VSD closure, and another patient with a significant residual shunt needed placement of an additional device in another session. The mean procedure time was 44 ± 2 min, with a mean fluoroscopy time of 12.8 ± 7.7 min. The mean follow-up duration was 11 ± 9.7 months (range, 6–35). Non-significant shunts were found in 32 patients (21.2%). Newly acquired valve regurgitation was observed in 16 patients (10.6%), including 11 patients (7.3%) with trivial-to-mild aortic regurgitation and 5 (3.3%) with moderate-to-severe tricuspid regurgitation. Electrophysiological adverse events occurred in 5 patients (3.3%), including nodal rhythm (n = 3, 2%), intermittent heart block (n = 1, 0.7%), and severe bradycardia (n = 1, 0.7%). Vascular complications were documented in 13 patients (8.6%) including one developing chronic vascular occlusion.ConclusionPercutaneous VSD closure with the MFO device is a safe, effective, and feasible procedure via both antegrade and retrograde approaches.